Investigating fine temporal dynamics of prosodic and lexical accommodation - BONIN, FRANCESCA; CAMPBELL, NICK; DE LOOZE, CELINE; VOGEL, CARL (INTERSPEECH, 2013)
Conversational interaction is a dynamic activity in which participants engage in the construction of meaning and in establishing and maintaining social relationships. Lexical and prosodic accommodation have been observed in many studies as contributing importantly to these dimensions of social interaction. However, while previous works have considered accommodation mechanisms at global levels (for whole conversations, halves and thirds of conversations), this work investigates their evolution through repeated analysis at time intervals of increasing granularity to analyze the dynamics of alignment in a spoken language corpus. Results show that the levels of both prosodic and lexical accommodation fluctuate several times over the course of a conversation.
14th Annual Conference of the International Speech Communication Association
PUBLISHED
Lyon
Keywords: prosodic accommodation; lexical alignment; dynamics; task-based interaction; linguistics; speech science; Digital Humanities; Intelligent Content & Communications; Computational linguistics